Evaluasi Hasil Quality Control (QC) Pemeriksaan Hemoglobin dan Trombosit Berdasarkan Westgard Rules dan Six Sigma di Rumah Sakit AMC Muhammadiyah - Miftahul Jannahti Putri; Woro Umi Ratih (Malahayati Nursing Journal, 2025)
ABSTRACT Quality control is part of the internal laboratory control procedures at the analytical stage to ensure that the results issued are correct and no errors occur in the examination process which is evaluated using westgard rules and six sigma. Based on the results of the preliminary study, the demand for hematology tests has increased so that quality control on the hematology analyzer is carried out every day, but has not used westgard rules and six sigma. This study aims to evaluate the results of quality control by assessing the level of precision and accuracy as well as westgard rules determined by the levey-jennings graph and six sigma. This type of research is a quantitative descriptive study with a cross-sectional approach with samples in the form of secondary data on the quality control results of hemoglobin and platelet examinations in November - December 2024, and January 2025 with total sampling techniques and processed with Microsoft Excel. The results showed that the accuracy (bias) and precision (CV) values of hemoglobin examination were -0,73% and 0,81% while platelet examination were -1,2% and 5,9%. Westgard rules found in both examinations were 1₂s, 2₂s, 4₁s, R₄s, and 10x rules. The sigma value obtained in the hemoglobin parameter was 10,5 while the sigma value of the platelet parameter was found to be 2,9. Based on the results of the study, it can be concluded that the accuracy and precision of the examination were good, there were random and systematic errors based on the westgard rule on both parameters, and the sigma were categorized as poor for platelets and world class for hemoglobin. Keywords: Quality Control of Hematology, Westgard Rules, Six Sigma ABSTRAK Quality control merupakan bagian dari prosedur kontrol laboratorium internal tahap analitik untuk memastikan hasil yang dikeluarkan tepat serta tidak terjadi kesalahan dalam proses pemeriksaan yang dievaluasi menggunakan westgard rules dan six sigma. Berdasarkan hasil studi pendahuluan, permintaan pemeriksaan hematologi meningkat sehingga quality control pada alat hematology analyzer dilakukan setiap hari, namun belum menggunakan aturan westgard dan six sigma. Penelitian ini bertujuan untuk mengevaluasi hasil quality control dengan menilai tingkat presisi dan akurasi serta aturan westgard yang ditentukan dengan grafik levey-jennings dan six sigma. Jenis penelitian merupakan penelitian deskriptif kuantitatif pendekatan cross-sectional dengan sampel berupa data sekunder hasil quality control pemeriksaan hemoglobin dan trombosit bulan November - Desember 2024, dan Januari 2025 dengan teknik total sampling serta diolah dengan Microsoft Excel. Hasil penelitian didapatkan nilai akurasi (bias) dan presisi (CV) pemeriksaan hemoglobin adalah -0,73% dan 0,81% sedangkan pemeriksaan trombosit -1,2% dan 5,9%. Aturan westgard yang ditemukan pada kedua pemeriksaan berupa aturan 1₂s, 2₂s, 4₁s, R₄s, dan 10x. Nilai sigma yang diperoleh pada parameter hemoglobin adalah 10,5 sedangkan nilai sigma parameter trombosit ditemukan angka 2,9. Berdasarkan hasil penelitian dapat disimpulkan bahwa akurasi dan presisi pemeriksaan baik, ditemukan adanya kesalahan acak dan sistematik berdasarkan aturan westgard pada kedua parameter, dan nilai sigma dengan kategori kurang baik untuk trombosit dan  kelas dunia  pada hemoglobin. Kata Kunci: Quality Control Hematologi, Westgard Rules, Six Sigma